Improving implementation of the Istanbul Programme of Action, goals and targets related to productive capacities and doubling the share of the least developed countries in global exports : executive summary (UN New YorkUS, 2017)
Discusses ways and means of improving the implementation of priority areas agreed in the Istanbul Programme of Action, and focuses on its goals and targets related to productive capacities and doubling the share of the least developed countries in global exports.
Keywords: PRODUCTIVITY